In Vivo Assessment of the Effect of CYP1A2 Inhibition and Induction on Pomalidomide Pharmacokinetics in Healthy Subjects. (15th May 2018) - Li, Yan; Liu, Liangang; Wang, Xiaomin; Zhang, Chengyue; Reyes, Josephine; Hoffmann, Matthew; Palmisano, Maria; Zhou, Simon
Abstract: Pomalidomide is an immunomodulatory drug, and the dosage of 4 mg per day taken orally on days 1‐21 of repeated 28‐day cycles has been approved in the European Union and the United States to treat patients with relapsed/refractory multiple myeloma. In vitro data showed that pomalidomide is a substrate of multiple cytochrome P450 (CYP) isozymes and that its oxidative metabolism is mediated primarily by CYP1A2 and CYP3A4, with minor contributions from CYP2C19 and CYP2D6. The effect of CYP1A2 inhibition by fluvoxamine (a strong CYP1A2 inhibitor) and CYP1A2 induction by smoking on pomalidomide pharmacokinetics in healthy subjects has been assessed in 2 separate phase 1 open‐label, single‐dose studies. Following administration of a single oral dose of 4 mg pomalidomide, the plasma exposure when coadministered with fluvoxamine was 225.1% and 123.7% of that when administered alone for the total plasma exposure (AUC0‐inf ) and the plasma peak exposure (Cmax ), respectively. In smokers with elevated CYP1A2 activity demonstrated by high caffeine clearance (a marker of CYP1A2 induction), the AUC0‐inf was 32.3% lower, whereas the Cmax was 14.4% higher than that in nonsmokers. In addition, pomalidomide was safe and well tolerated as a single oral dose of 4 mg in healthy male smokers and nonsmokers ≥ 40 to ≤ 80 years old, and a single oral dose of 4 mg pomalidomide coadministered with multiple oral 50‐mg doses of the CYP1A2 inhibitor fluvoxamine compared with pomalidomide alone was safe and well tolerated by the healthy male subjects.